2019
DOI: 10.1177/0363546519881420
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Osteochondral Transplantation for Large Osteochondral Lesions of the Talus Is a Viable Option in an Athletic Population

Abstract: Background: Autologous osteochondral transplantation (AOT) has been shown to be a viable treatment option for large osteochondral lesions of the talus. However, there are limited data regarding the management of large lesions in an athletic population, notably with regard to return to sport. Our investigation focused on assessing both qualitative and quantitative outcomes in the high-demand athlete with large (>150 mm2) lesions. Hypothesis: AOT is a viable option in athletes with large osteochondral lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 20 publications
1
48
0
Order By: Relevance
“…As patients with OLT with subchondral cysts greater than 6 mm in depth do not do well with conventional marrow stimulation techniques, autologous/allogeneic osteochondral or autologous chondrocyte transplantation is recommended (7,20). Although osteochondral autograft or allograft transplantation may be a reasonable option for Hepple stage V OLT (21), it still has problems such as undesirable donor site morbidity, which was reported in 16.9% of cases in the knee-to-ankle procedure (22), malunion, or non-union. Therefore, the objective of this study was to retrospectively evaluate the postoperative clinical scores and MRI findings of a novel method with calcaneus bone graft transplantation for patients with Hepple stage V OLT under arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…As patients with OLT with subchondral cysts greater than 6 mm in depth do not do well with conventional marrow stimulation techniques, autologous/allogeneic osteochondral or autologous chondrocyte transplantation is recommended (7,20). Although osteochondral autograft or allograft transplantation may be a reasonable option for Hepple stage V OLT (21), it still has problems such as undesirable donor site morbidity, which was reported in 16.9% of cases in the knee-to-ankle procedure (22), malunion, or non-union. Therefore, the objective of this study was to retrospectively evaluate the postoperative clinical scores and MRI findings of a novel method with calcaneus bone graft transplantation for patients with Hepple stage V OLT under arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…OAT was used to treat the patients with large subchondral cysts. A number of studies have reported good to excellent outcomes of MF and OAT at a mid-term follow-up [27][28][29][30][31][32]. Besides the management of intraarticular lesions, lateral ligaments reconstruction was performed for the patients combined with CAI.…”
Section: Discussionmentioning
confidence: 99%
“…Osteochondral autograft transplantation (OAT) fills the defect site with osteochondral autograft collected from less weight-bearing portions of the joint, which may lead to donor site lesion [ 13 ]. In the case of large osteochondral lesion, in which multiple osteochondral autografts are necessary to fill the defect, the risk of donor site morbidity might increase with the number of used autologous osteochondral plugs [ 14 ].…”
Section: Current Clinical Therapies For Ocdsmentioning
confidence: 99%